On the reduction of LP problem - Nykowski, Ireneusz (The Institute Of National Planning., 2018)
And during computational procedure LP problems reduction prior to optimal solutions finding/is discussed in this paper. So, the notions of redundant constraints conditionally redundant constraint and conditionally redundant variables are introduced.